A inclusão do ensino de música nos currículos escolares do CRAJUBAR: contribuições do estágio supervisionado do curso de licenciatura em música da UFC - Campus Cariri - Ferro, Ítalo Rômulo de Holanda (2013)
This dissertation work had its development in the Post-Graduate Education Brazilian FACED - Faculty of Education of the Federal University of Ceará in the search line Education, Curriculum and Teaching and thematic Music Education. This research conducted an analysis of how the experiences of students by selecting the Bachelor of Music from UFC - Cariri who perform the Supervised contribute in the process of inclusion of music education in school curricula of Crajubar. The whole process of research was focused on the theoretical and practical actions of students of music directly involved Supervised schools. As methodological procedure, used the technique of qualitative social research Focus Group as a form of integrative methodologic that allows democratic debate of the experiences gained by students in supervised training in music education. From the results of this research have elaborated some recommendations with the aim of contributing to the harmonious relationship between the formation of competent teachers by the university and the process of inclusion of music education in the schools of the region.